Dual Ni/photoredox-catalyzed asymmetric cross-coupling to access chiral benzylic boronic esters - Purui Zheng (Nature Portfolio, 2021)
Metallaphototoredox catalysis has been rarely applied to reductive cross-couplings, in contrast to typical redox-neutral methods. Here, the authors report a mild Ni/photoredox-catalyzed reductive cross-coupling of aryl iodides and α-chloroboranes, further enriching the metallaphotoredox chemistry.